Imprints of Different Types of Low-angular-momentum Accretion Flow Solutions in General Relativistic Hydrodynamic Simulations - Indu K. Dihingia; Akhil Uniyal; Yosuke Mizuno (The Astrophysical Journal)
Depending on the astrophysical source and its environment, the accretion flows can exhibit a variety of behaviors and characteristics in accordance with the type of solutions. We study low-angular-momentum accretion flows onto black holes using 2D general relativistic hydrodynamic simulations to find imprints of different types of accretion solutions. Such flows, relevant to X-ray binaries and wind-fed low-luminosity active galactic nuclei, often lack sufficient angular momentum to form standard accretion disks. We initialize simulations with semianalytical transonic solutions defined by specific energy ( ${{ \mathcal E }}_{0}$ ) and angular momentum ( λ _0 ), allowing a systematic classification of flow types with: (i) an outer sonic point, (ii) an inner sonic point, and (iii) both, exhibiting shock transitions. Only solutions with two sonic points produce hot, thermally driven bipolar jets/outflows with Lorentz factors up to γ  ∼ 2, despite the absence of magnetic fields. Using a general relativistic radiation transfer calculation, we compute broadband spectra and images at X-ray (1 keV) from bremsstrahlung emission. Radiative properties depend strongly on the type of accretion solution. Solutions with inner sonic points produce the brightest and most extended X-ray emission, while outer-point solutions produce compact, fainter signals. These multidimensional models are thus essential for predicting radiative signatures and will enable the development of semianalytical tools for interpreting X-ray binaries and possibly Sgr A* in weak magnetic field regimes.